Students’ Perceptual Experience on Using Video in Learning English Vocabulary - Angga Fitransah; Sukristiningsih Sukristiningsih; Hengki Mofu; Suardi Sahid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Learning a language requires a large range of vocabulary in its language to position a learner on the communication level. Consequently, teaching vocabulary is spotted as important since it is becoming a key component of language proficiency and as basis of learners to develop their listening, speaking, reading and writing. Media in teaching vocabulary becomes significant as media existence is to help teachers to deliver the topic and help learners to easily understand the topic. There are many types of media available, and video is one of them. The recent study focuses on students’ perceptual experience on using video in learning English vocabulary at the 10th grade students of SMA Oikoumene in Manokwari, Papua Barat Province, and the hindrance faced by students. Therefore, to meet the aims, a questionnaire and an open-ended question were employed to collect the data from 23 participants filled the questionnaire and 10 participants interviewed. There were 20 items on the questionnaire which grouped into three themes namely general information related to the use of video in learning vocabulary, using video support students’ learning, and video motivate students. The data presented that the score of each theme was 3.00 which categorized as positive, and the biggest obstacle faced by students were the unstable internet networking and run out of credit. Finally, the use of video in teaching English at SMA Oikoumene Manokwari has to be kept up due to support and motivate students learning.